32nd Structures, Structural Dynamics, and Materials Conference 1991
DOI: 10.2514/6.1991-1140
|View full text |Cite
|
Sign up to set email alerts
|

Progressive fracture in composites subjected to hygrothermal environment

Abstract: The influence of hygrothermal environmental conditions on the load carrying ability and response of composite structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The use of computer-based computational modeling to evaluate the service life (i.e., durability and reliability) of Polymer Matrix Composite (PMC) structures has been under development by NASA Lewis/ Langley [11][12][13][14][15][16] for several years, with the result that computer codes have become available for evaluation of PMC structures under service conditions. The use of computer-based computational modeling to evaluate the service life (i.e., durability and reliability) of Polymer Matrix Composite (PMC) structures has been under development by NASA Lewis/ Langley [11][12][13][14][15][16] for several years, with the result that computer codes have become available for evaluation of PMC structures under service conditions.…”
Section: -14mentioning
confidence: 99%
“…The use of computer-based computational modeling to evaluate the service life (i.e., durability and reliability) of Polymer Matrix Composite (PMC) structures has been under development by NASA Lewis/ Langley [11][12][13][14][15][16] for several years, with the result that computer codes have become available for evaluation of PMC structures under service conditions. The use of computer-based computational modeling to evaluate the service life (i.e., durability and reliability) of Polymer Matrix Composite (PMC) structures has been under development by NASA Lewis/ Langley [11][12][13][14][15][16] for several years, with the result that computer codes have become available for evaluation of PMC structures under service conditions.…”
Section: -14mentioning
confidence: 99%
“…Previous researchers predicted the influence of an existing notch, as well as loading on the safety and durability of fiber composite specimens by tracking the damage growth and propagation. Minnetyan et al [2][3][4][5] and Huang et al [6,7] have demonstrated that computational simulations can be used to evaluate the fracture characteristics of composite structures under various loading and environmental conditions. [8] modeled C(T) specimens and identified the damage initiation, growth, and propagation processes for cross-ply laminated specimens.…”
Section: Introductionmentioning
confidence: 99%
“…[8] modeled C(T) specimens and identified the damage initiation, growth, and propagation processes for cross-ply laminated specimens. However, most of the previous investigations [2][3][4][5][6]8] focused on cross-ply and angle-ply laminated composites. Since biaxial braided fiber composites have many advantages over conventional laminated composites and are used frequently in aerospace and automobile components, it is essential to develop an effective computational capability to predict fracture behavior of biaxially braided composites.…”
Section: Introductionmentioning
confidence: 99%
“…The present computational approach has previously been used for the investigation of the behavior of conventional laminated composite structures, including the effects of composite degradation on structural response (Minnetyan et al, 1992), composite structures global fracture toughness (Minnetyan et al, 1990), effect of the hygrothermal environment on durability (Minnetyan et al, 1992a), damage progression in stiffened composite shells (Minnetyan et al, 1992b), the behavior of discontinuously stiffened composite panels under loading (Minnetyan et al, 1995), damage propagation in thick composite shells under external pressure (Minnetyan and Chamis, 1997), damage and fracture progression in CFRP I-beams with three different lay-ups (Huang and Minnetyan, 1998). Further degradation is in the form of additional cracking, delamination, and fiber fractures that may lead to structural fracture.…”
Section: Introductionmentioning
confidence: 99%